Perancangan Video Pariwisata Kawah Wurung Bondowoso Sebagai Media Promosi - Dwi Cahyaningtyas Mulyani; Pujiyanto Pujiyanto; Rina Nurfitri (LPPM STIKI Malang, 2020)
Bondowoso is one of the regencies in Indonesia that has potential, including its natural tourism potential. Bondowoso is the only district in the “Tapal Kuda” area that does not have a coastline. Many potential tourism objects owned by Bondowoso Regency, one of which is